1999
DOI: 10.1074/jbc.274.45.32015
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of a Cytosolic and Nuclear O-GlcNAc Transferase

Abstract: The O-GlcNAc transferase (OGT) is a unique nuclear and cytosolic glycosyltransferase that contains multiple tetratricopeptide repeats. We have begun to characterize the mechanisms regulating OGT using a combination of deletion analysis and kinetic studies. Here we show that the p110 subunit of the enzyme forms both homoand heterotrimers that appear to have different binding affinities for UDP-GlcNAc. The multimerization domain of OGT lies within the tetratricopeptide repeat domain and is not necessary for acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
404
0
6

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 389 publications
(427 citation statements)
references
References 38 publications
17
404
0
6
Order By: Relevance
“…Although the expression of full-length ncOGT was not significantly altered in activated T cells, we noted a striking difference in the expression levels of sOGT and possibly mOGT. Because OGT is thought to function as a heterotrimer composed of two ncOGT subunits and one sOGT subunit (73), changes in the relative expression of these subunits may influence substrate specificity or enzymatic activity. Studies with recombinant OGT showed that certain substrates are only modified by specific isoforms (74).…”
Section: Discussionmentioning
confidence: 99%
“…Although the expression of full-length ncOGT was not significantly altered in activated T cells, we noted a striking difference in the expression levels of sOGT and possibly mOGT. Because OGT is thought to function as a heterotrimer composed of two ncOGT subunits and one sOGT subunit (73), changes in the relative expression of these subunits may influence substrate specificity or enzymatic activity. Studies with recombinant OGT showed that certain substrates are only modified by specific isoforms (74).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the structure of OGT and the TPR domain have been solved (Lazarus et al 2011;Martinez-Fleites et al 2008;Jinek et al 2004). The TPR domain forms an extended alpha-helix similar to importin-α (Jinek et al 2004), and is important for mediating protein-protein interactions and enzyme activity (Kreppel and Hart 1999;Lubas and Hanover 2000). The catalytic domain contains two Rossman folds, separated by an intervening sequence.…”
Section: O-glcnac Transferasementioning
confidence: 99%
“…Furthermore, insulin stimulation recruits OGT from the nucleus to the plasma membrane, wherein OGT catalyzes O-GlcNAcylation on some insulin signaling proteins and attenuates its signal transduction by altering their phosphorylation status, and hepatic overexpression of OGT impairs the transcription of insulin-responsive genes and causes the perturbation of insulin-induced inhibition of gluconeotransfer of a single GlcNAc from UDP-GlcNAc to serine/threonine residues of substrate proteins 25,26) ; whereas OGA catalyzes the removal of the GlcNAc from such residues 27,28) . Since the affinity of OGT for substrate proteins is highly sensitive to the intracellular UDP-GlcNAc level 29) , glucose flux via the hexosamine biosynthetic pathway directly influences O-GlcNAc levels. Indeed, hyperglycemia 30) , glucosamine infusion 30) , GLUT overexpression 31) , and GFAT overexpression 32) , all of which increase flux via the hexosamine biosynthetic pathway, result in increased intracellular UDP-GlcNAc and OGlcNAc levels.…”
Section: O-glcnacylationmentioning
confidence: 99%
“…OGT catalyzes the transfer of a single GlcNAc from UDP-GlcNAc to serine/threonine residues of substrate proteins 25,26) , while OGA catalyzes the removal of the GlcNAc from such residues 27,28) . The affinity of OGT for substrate proteins is highly sensitive to the intracellular UDP-GlcNAc level 29) . …”
Section: O-glcnacylationmentioning
confidence: 99%